New data on the spider fauna of Iran (Arachnida: Araneae), Part XI - Zamani, Alireza (Tarbiat Modares University, 2025)
New faunistic and taxonomic data are provided for 18 families of Iranian spiders. Four species, Cryptodrassus liyanicus Zamani & Marusik, sp. n. (♀, Bushehr Province; Gnaphosidae), Mesiotelus khorasanicus Zamani & Marusik, sp. n. (♂♀, Razavi Khorasan Province; Liocranidae), Nurscia minuscula Zamani & Marusik, sp. n. (♀, West Azerbaijan Province; Titanoecidae) and Talanites farsensis Zamani & Marusik, sp. n. (♀, Fars Province; Gnaphosidae), are described as new to science. Clubiona liachviana Mcheidze, 1997 stat. reval. (Clubionidae) is removed from the synonymy with C. alpicola Kulczyński, 1882 and is reported from Armenia, Azerbaijan, Iran and Turkmenistan for the first time; additionally, its previously unknown male is described. The genus Kishidaia Yaginuma, 1960 (Gnaphosidae) and a total of 10 species are recorded in Iran for the first time, and new provincial records are provided for 20 species. Two specimens from Iraq are also reported. Considering the results of this paper, the number of species of spiders known from Iran is increased to 980 species in 329 genera.